The surface tension and interfacial composition of water/ethanol mixture - Phan, Chi (ELSEVIER, 2021)
This study develops a model to fit the surface tension of the water/ethanol mixture for the complete composition range from 0 to 1. The theoretical framework complements Van Der Waals theory on the density gradient. The modelling results overcome the limitation of Gibbs adsorption isotherm, which completely ignores the composition of the interfacial layer. Furthermore, the model presents a new method to correctly calculate the composition of the interfacial layer for binary liquid mixture and surfactant solutions.